2023
DOI: 10.3390/mti7020011
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Big Five Personality Traits with Training Effectiveness, Sense of Presence, and Cybersickness in Virtual Reality

Abstract: Virtual reality (VR) presents numerous opportunities for training skills and abilities through the technology’s capacity to simulate realistic training scenarios and environments. This can be seen in how newer research has emphasized how VR can be used for creating adaptable training scenarios. Nevertheless, a limited number of studies have examined how personality traits can influence the training effectiveness of participants within VR. To assess individual preferences in a virtual environment, the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…The analyses showed SS to impact spatial ability significantly negatively in the IVR condition group (β = −.52, p = .011) but not a significant effect in the non-immersive setting (p = .084). This aligns with previous studies finding that SS hinders individuals' ability to interact, perform, and learn in a VE (see Thorp et al, 2023). Additionally, the result is following several studies that found higher levels of immersion to be associated with higher SS (Polcar and Horejsi, 2015;Kwok et al, 2018;Martirosov et al, 2022).…”
Section: Sop CL and Ss On Spatial Abilitysupporting
confidence: 91%
See 3 more Smart Citations
“…The analyses showed SS to impact spatial ability significantly negatively in the IVR condition group (β = −.52, p = .011) but not a significant effect in the non-immersive setting (p = .084). This aligns with previous studies finding that SS hinders individuals' ability to interact, perform, and learn in a VE (see Thorp et al, 2023). Additionally, the result is following several studies that found higher levels of immersion to be associated with higher SS (Polcar and Horejsi, 2015;Kwok et al, 2018;Martirosov et al, 2022).…”
Section: Sop CL and Ss On Spatial Abilitysupporting
confidence: 91%
“…The participants in the IVR condition (N = 32, 18 males, 14 females) were 22.91 years on average (SD = 1.57). The SoP score (5.23) for the IVR condition was generally in line with similar studies (Weech et al, 2019;Thorp et al, 2023), and the SS was generally in line with most VR studies (e.g., Somrak et al, 2019, which reports scores ranging from 45.95 to 56.41 for different HMD models). CL scores (M = 8.29) were similar to the 2D condition (M = 8.31), contradicting previous studies finding CL to be higher in IVR (Makransky et al, 2019;Breves and Stein, 2023).…”
Section: Descriptivessupporting
confidence: 82%
See 2 more Smart Citations
“…Second, various previous studies have shown that individual personality traits are another possible factor affecting perceived realism in VR. For instance, personality traits such as anxiety [13], introversion, [31] agreeableness, and conscientiousness [32] have been shown to be associated with a sense of presence in VR. However, in this study, we did not select the personality questionnaires typically used in other VR studies.…”
Section: B Related Work On the Factors Influencing Perceived Realismmentioning
confidence: 99%